Peaceful Technology: Social Media And Virtuous Conduct : an Interview with S. Joshua Swamidass - Metzger, Paul Louis (Cultural encounters, 2022)
This interview with S. Joshua Swamidass, physician, scientist, and founder of Peaceful Science, aims at fostering virtuous and peaceful conduct in public discourse. The exchange includes consideration of social media. Swamidass highlights the importance of public debate and the need to safeguard against compartmentalizing ourselves from others with divergent views. Similarly, he speaks about the need to humanize our debate partners and reward news outlets and algorithms that foster constructive interaction between opposing positions. Swamidass maintains that the actual and virtual worlds are not separate and that persons are involved in both forms of engagement. Nor is actual or artificial intelligence review immune to error in adjudicating between healthy and unhealthy discourse. We must remain vigilant to improve public discourse in various settings rather than become complacent. Hopefulness and a desire to cultivate peaceable and enlightening exchanges consisting of diverse perspectives are critical to human and societal flourishing.